Study on the Dependence of Sun Protection Factor on Particle Size Distribution of Mica Using Gravitational Field‐Flow Fractionation - Kim, Ji Hye; Choi, Jaeyeong; Choi, Seongho; Kim, Woonjung; Lee, Seungho (Bulletin of the Korean Chemical Society, 2020)
Sunlight consists of beams of light of broad wavelength ranges, including infrared, visible, and ultraviolet (UV) radiation; X‐rays; and γ‐rays. Although the UV content of sunlight is relatively low, the human body, especially the human skin, is sensitive to UV rays. Mica is known to be effective in protecting the human skin from sunlight and reduces fine lines and pores on the skin. Mica is currently used as a coloring agent in various sunscreen products. Still, there is no detailed report on the effect of mica on the sun protection factor (SPF). In this study, effects of the particle size, particle size distribution, and the content of mica on SPF were studied. Gravitational field‐flow fractionation (GrFFF) was employed to analyze the particle size and the particle size distribution of the mica particles. GrFFF provided size‐based separation of the mica particles and was useful for determining the size distributions and average sizes of the mica particles. It was found that the mixing ratio (in wt %) of 3:3:4 of TiO2:octyl methoxycinnamate:mica yielded the highest SPF. Generally, the SPF tends to increase with increasing particle size of the mica.